2022
DOI: 10.1111/jfpp.16405
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐storage application of L‐arginine mitigates chilling injury and maintains quality of Sandhuri guava fruit

Abstract: Guava being highly chilling sensitive fruit exhibits limited storability. In two separate studies, guava cv. Sandhuri fruit treated with L-arginine (0, 1, 2, or 3 mM) were kept at either 10 ± 1°C with 90 ± 5% RH (Study-1) and 5 ± 1°C with 90 ± 5% RH (Study-2).Results indicated that application of 1 mM arginine was effective for maintaining higher firmness (16.17 N), total soluble solids (4.9°Brix), carotenoids (3.01 mg 100 ml −1 FW) at 10°C. However, no signs of chilling injury (CI) were observed in guava when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Nitric oxide plays significant role in delaying senescence and improving cellular permeability by eliminating ROS, thereby reducing cell membrane permeability and preventing rapid dehydration of the persimmon fruit and rapid weight loss during storage period [ 12 , 13 ]. Ali et al [ 40 ] showed in “Sandhuri” guava fruit that arginine application decreased the weight loss by the maintenance of membrane integrity during low-temperature storage. The results confirmed the results of the Hasan et al [ 12 ] study on cucumbers treated with L-arginine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitric oxide plays significant role in delaying senescence and improving cellular permeability by eliminating ROS, thereby reducing cell membrane permeability and preventing rapid dehydration of the persimmon fruit and rapid weight loss during storage period [ 12 , 13 ]. Ali et al [ 40 ] showed in “Sandhuri” guava fruit that arginine application decreased the weight loss by the maintenance of membrane integrity during low-temperature storage. The results confirmed the results of the Hasan et al [ 12 ] study on cucumbers treated with L-arginine.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in carotenoid concentration during storage occurs as a consequence of the postharvest ripening process as well as the reduction in TA and firmness. Therefore, the effect of L-arginine treatment on delaying the changes of these parameters could be attributed to a delay of the postharvest ripening process throughout an increment of the activity of the antioxidative enzymes, which are involved in reducing reactive oxygen radicals based damages [ 12 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The authors noticed a strong correlation between higher SOD, POD, and CAT activities and higher eating quality in 200 ppm ascorbic acid (AA)treated than AA-untreated guava fruits. Similar works have been conducted, mostly aiming to improve the storability and shelf life of guava fruits using different treatments such as chitosan coating (Hong et al, 2012), melatonin (Fan et al, 2022), L-arginine (Ali et al, 2022), and near-freezing temperature (Xiao et al, 2022). The main focus is to maintain fresh-like quality traits of guava fruits, which are highly perishable and deteriorate quickly under storage.…”
Section: Crop Sciencementioning
confidence: 98%